A Hybrid Retrieval Method for an Ω-Class Bianisotropic Metamaterial Using Scattering Parameter Method - Gokhan Ozturk; Ugur Cem Hasar; Yunus Kaya; Huseyin Korkmaz; Ivaylo Stoyanov (IEEE Access)
In this study, a hybrid retrieval method is proposed to retrieve all terms in the electric and magnetic tensors (along with coupling tensors) of $Ω $ -class bianisotropic metamaterial (MM) slabs using scattering (S-) parameters of both normal incidence TE2 mode and oblique incidence TM2 and TE modes. Compared with other extraction methods in the literature, our retrieval method fully characterizes the MM slab (extracts all constitutive parameters) without necessitating any numerical technique (non-iterative) using fewer wave configurations (two modes) and sample configurations (one configuration). Contrary to two sample configurations required in the application of previous retrieval methods in the literature, one sample configuration (with and without its rotation in the transverse plane) significantly decreases the effect of fabrication tolerances on the accuracy of extraction. The proposed extraction method is first validated by a bulk MM slab synthesized by the Lorentz and Drude models. Then, it is applied for extracting the electromagnetic properties of two bianisotropic MM slabs in the form of square split-ring-resonators and $Ω $ -shape using their S-parameters simulated by a full wave simulation program. Finally, its accuracy is examined by comparing simulated S-parameters with those reconstructed by using extracted electromagnetic parameters. It is observed that our proposed method determines the constitutive parameters with a relatively higher accuracy in a relatively short amount of time.